Regulation of Copyright Certificate As A Material Guarantee and Bankrupt Estate/Beodel In Indonesia - Ni Luh Putu Geney Sri Kusuma Dewi; Putu Eka Trisna Dewi; Ni Putu Riyani Kartika Sari (ADI Journal on Recent Innovation, 2021)
The existence of copyright as one type of intangible objects (intangible) in the development of the business and economic world is used as guarantee assets in banking and general confiscation of debtor assets declared bankrupt. The use of copyright then creates problems in its application both in terms of regulation and how to interpret the value of the copyright. This study uses a type of library research with the approach of legislation and legal comparison. The results of this study indicate that copyright can be used as an object of collateral in guaranteeing debtor debt through the imposition of fiduciary collateral but there are obstacles in realizing it both in terms of regulations and the approach used in interpreting its value. There is also a vagueness of norms related to copyright regulation as an object that can be used as a bankruptcy in the Bankruptcy and Debt Delay Obligation Act so that justice, benefit and legal certainty cannot be realized in settling debts through bankruptcy institutions.